Prevalence and Relevance of Pruritus in Pregnancy. (25th September 2017) - Szczęch, Justyna; Wiatrowski, Artur; Hirnle, Lidia; Reich, Adam
Abstract : Pregnant women are at greater risk to suffer from chronic pruritus, but data on this symptom in this group is very limited. The aim of this study was to investigate the prevalence, clinical characteristics, and the importance of pruritus in pregnant women. A total of 292 consecutive pregnant women at the 33.0 ± 6.1 weeks of gestation (WoG) were recruited into this prospective, cross-sectional study. All patients underwent thorough anamnesis and detailed physical examination with the special emphasis on pruritus. Pruritus was assessed according to Visual Analogue Scale (VAS). Quality of life was measured with the Dermatology Life Quality Index (DLQI). The point prevalence of pruritus was 20.2% (n = 59 ), while pruritus prevalence during the entire pregnancy was 38.0% (n = 111 ). Pruritus started on average at the 27.2 ± 7.6 WoG; it was significantly more common among women in third trimester. The mean VAS was 4.8 (±2.4) points. The DLQI scoring significantly correlated with VAS (r = 0.52, p < 0.001 ). Based on the results of our study about one-third of women suffer from pruritus during pregnancy. Many of them find it a very distressing and disturbing symptom.